Apathy, alexithymia, and depressive symptoms: Points of convergence and divergence. (30th October 2016) - Ready, Rebecca E.; Mather, Molly A.; Santorelli, Gennarina D.; Santospago, Breanna P.
Abstract: This study determined convergence and divergence in the constructs of alexithymia, apathy, and depressive symptoms. Understanding of similarities and differences between these constructs will improve diagnostic accuracy for clinical and research purposes. Community-dwelling participants ( N =622, M age=35.6 years, SD =13.1) completed online measures of alexithymia, depression, and apathy; 12.2% were alexithymic, 37.8% reported significant depressive symptoms, and 24.9% reported significant apathy. Exploratory Factor Analyses (EFAs) determined the best factor structure for the apathy, alexithymia, and depressive symptoms was comprised of three factors and accounted for 45.1% of item variance. The Depression, Apathy, and Alexithymia factors were defined most strongly by item content that is at the core of each construct. Depression was defined most highly by items assessing sadness, low self-esteem, and loneliness. The strongest item loadings for Alexithymia were difficulty identifying and describing feelings. Apathy was characterized by poor motivation, low interest, and lack of initiative. However, each of these core and defining features had significant cross-loadings on one of the other two factors. Negative affect shared variance with Apathy, low motivation shared variance with Depression, and difficulty describing and identify feelings shared variance with Depression and Apathy. Clinical and research implications are discussed. Highlights: Depression characterized by sadness, low self-esteem, and loneliness. The core of Alexithymia is difficulty identifying and describing feelings. Apathy characterized by poor motivation, low interest, and lack of initiative. Depression, Alexithymia, and Apathy had cross-loadings on one other factor. No item content was overlapping with Depression, Alexithymia, and Apathy.